A Comparative Analysis of the Views of Zimbabwean Rural and Urban Adolescents on Childrenâs Household Work - Mushoriwa, T.D.; Chitsamatanga, B.B.; Mbokochena, E (SOSIOHUMANIKA, 2013)
ABSTRACT: It is important to study childrenâs views on the household work they perform, because the studies, for example J.J. Goodnow (1996), have again and again demonstrated that the way children are brought up directly impacts on their future lives. How children are treated and the work that they are expected to accomplish in the home have a bearing on almost all aspects of their development. This article presents the results of a study on the views of rural and urban adolescents on childrenâs household work. Specifically, the study-tapped adolescentsâ views regarding the age at which children should begin household work, the value of childrenâs household work, and whether children should be remunerated for doing household work. A total of 200 adolescents were involved in this study. Data were collected from the respondents through a questionnaire supplemented by interviews. A crosstab was used to report results in percentages. Generally, there was support for childrenâs household work, especially from rural respondents. The majority of the respondents felt that children should begin household work between 8 and 10 years and that they should not be paid for such work. The study recommended, among other things, that both rural and urban children should help with household chores, but they should be afforded opportunities to study and to play.KEY WORD: Household work, views of rural and urban adolescents, comparative analysis, Zimbabwean society, and study and play.Â RESUME: Artikel ini berjudul âSebuah Analisis Perbandingan tentang Pandangan Remaja Pedesaan dan Perkotaan di Zimbabwe Mengenai Pekerjaan Anak dalam Rumah Tanggaâ. Sangat penting untuk mempelajari pandangan anak-anak pada pekerjaan rumah tangga mereka, karena studi-studi, misalnya J.J. Goodnow (1996), telah berulang kali menunjukkan bahwa cara anak-anak yang dibesarkan secara langsung berdampak pada kehidupan masa depan mereka. Bagaimana anak-anak diperlakukan dan pekerjaan yang harus mereka capai di rumah memiliki pengaruh pada hampir semua aspek perkembangan mereka. Artikel ini menyajikan hasil studi tentang pandangan remaja pedesaan dan perkotaan pada pekerjaan anak di rumah tangga mereka. Secara khusus, studi ini bertumpu pada pandangan remaja mengenai usia berapa anak-anak harus mulai bekerja dalam rumah tangga, nilai pekerjaan rumah tangga anak, dan apakah anak-anak harus dibayar untuk melakukan pekerjaan rumah tangga mereka. Sebanyak 200 remaja terlibat dalam penelitian ini. Data dikumpulkan dari responden melalui kuesioner yang dilengkapi dengan wawancara. Sebuah tabel silang digunakan untuk melaporkan hasil dalam persentase. Umumnya, ada dukungan untuk pekerjaan anak-anak dalam rumah tangga, terutama dari responden pedesaan. Mayoritas responden merasa bahwa anak-anak harus mulai mengerjakan pekerjaan rumah tangga antara usia 8 dan 10 tahun dan bahwa mereka tidak harus dibayar untuk pekerjaan tersebut. Studi ini merekomendasikan, antara lain, bahwa anak-anak, baik di pedesaan maupun di perkotaan, harus membantu pekerjaan rumah tangga, tetapi mereka harus diberikan kesempatan untuk belajar dan bermain.KATA KUNCI: Pekerjaan rumah tangga, pandangan remaja pedesaan dan perkotaan, analisis komparatif, masyarakat Zimbabwe, serta belajar dan bermain.Â Â Â Â About the Authors: Prof. Dr. T.D. Mushoriwa is a Lecturer at the Faculty of Education UFH (University of Fort Hare), Alice Campus 5700, South Africa; B.B. Chitsamatanga is a Lecturer at the Faculty of Education UFH; and E. Mbokochena is a Lecturer at the Womenâs University in South Africa. The corresponding author is: Tmushoriwa@ufh.ac.zaHow to cite this article? Mushoriwa, T.D., B.B. Chitsamatanga & E. Mbokochena. (2013). âA Comparative Analysis of the Views of Zimbabwean Rural and Urban Adolescents on Childrenâs Household Workâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.2 [November], pp.117-124. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 5, 2013); Revised (October 9, 2013); and Published (November 20, 2013). Â  Â